Implications of the downstream handling of captured CO2 - Mason, Fred; Stokes, Gerald; Fancy, Susan; Sick, Volker (Frontiers in Climate, 2023)
Carbon dioxide capture, utilization, and sequestration (CCUS) is a collection of approaches needed to supplement other efforts to achieve net zero carbon emissions. The specific combination of CO2 sources and sinks (a “usage pathway”) determines the environmental impact, economic viability, overall role in climate change mitigation and continued availability of carbon-based products. Optimal deployment requires a clear understanding of the nature of carbon sources and the durability and economic value of downstream processes and materials. Rigorous life cycle and techno-economic assessments (LCA and TEA) are critical. This paper presents a CO2 sources and sinks matrix as the high-level basis for assessing a usage pathway’s climate relevance and economics.